Filmes de anima??o da educa??o ambiental: uma contribui??o pedag?gica para a forma??o de professores das escolas do municipio de Feira de Santana - BA - Amorim, Camilla Ferreira (2024)
This dissertation has the general objective of analyzing the use of animated films as a pedagogical tool for Environmental Education in elementary school in the final years, based on a study with teachers from the municipal network of Feira de Santana - BA. As well as developing a teaching guide on animated films for the transposition of Environmental Education content. The research is of a qualitative-quantitative nature and had among the methodological procedures, data collection, which involved a bibliographical survey, analysis of the Curricular Proposal for Elementary Education of the Municipal Public Network of Feira de Santana ? BA, in addition to the application of questionnaires and conducting interviews with teachers from the municipal network of Feira de Santana ? BA. The data was then analyzed and discussed, serving as a basis for the development of the Educational Product entitled ?Sustainable Animation: A didactic guide for environmental education through cinema?. Regarding the analysis of the Curricular Proposal, it was found that the document does not provide an approach focused on Environmental Education. In turn, the data collected from the questionnaires revealed that the most frequently mentioned pedagogical strategy is films, with animations being the most cited film genre. The interviews showed that the majority of participants aim to use animated films, pedagogical innovation and emotional connection to discuss themes that permeate Environmental Education, and that the majority carry out post-film reflection activities, allowing students to develop critical skills. In relation to the Didactic Guide, as part of the educational product, an Animated Film Manual was prepared and as a suggestion for activities, pilot workshops were developed with the films ?The Lorax - In Search of the Lost Tr?fula? and ?Bee Movie?. The research allowed the conclusion that the majority of subjects participating in the research use animated films as a pedagogical strategy sporadically to discuss topics covered in Environmental Education, however the greatest difficulty in using these tools is related to school infrastructure. Furthermore, it is believed that the Didactic Guide contributes to the continuous development of teachers, encouraging the use of animated films as a tool to encourage discussions and expand information on environmental issues in the classroom.